The relationship between oil, renewable energy, inflation and sustainable development goals in opec and non-opec countries - Chen, Rongxin (2024)
The energy factor is critical to achieving the Sustainable Development Goals. Due to a lack of research comparing different energy perspectives with the SDGS, this paper examines the relationship between oil dynamics (including oil production and consumption), renewable energy, inflation, and the achievement of the Sustainable Development Goals (SDGS), focusing on OPEC and non-OPEC countries from 2000 to 2022. Through quantitative analysis, using fixed effects models and random effects models with panel data, the study examines how fluctuations in oil production and consumption, as well as renewable energy adoption and inflation, are linked to progress towards achieving the SDGS. The results show that renewable energy consumption and oil consumption have a positive impact on the overall achievement of the SDGS, but oil production has a negative impact on the overall achievement of the SDGS. In addition, the surprising result is that oil consumption contributes more to the achievement of the Sustainable Development Goals and only negatively impacts climate change (SDG13). This shows that the dynamics of the energy sector have complex implications for sustainable development. The study provides empirical evidence for the impact of oil and renewable energy on sustainable development and provides insights for decision-makers and stakeholders in energy planning and sustainable development strategies. The study highlights the urgent need for a balanced approach to energy management, emphasizing the transition to renewable energy to ensure long-term sustainability and achieve the Sustainable Development